Performance Measurement of Green Manufacturing in the Refined Sugar Industry Using the Green Supply Chain Operation Reference Approach at PT. ABC - Asnidar, Asnidar; Fole, Asrul; Malik, Rahmaniah; Ahmad, Arfandi (PT. SAFARI AMALIA, 2024)
The manufacturing industry, including the refined sugar industry, faces challenges in minimizing environmental impact and enhancing operational sustainability. The implementation of the green manufacturing concept is essential to achieving these goals. This study aims to evaluate the green manufacturing performance of PT. ABC, focusing on environmental, economic, and social aspects. The research methodology employed is a qualitative and quantitative descriptive analysis using relevant frameworks and metrics based on the Green SCOR. The findings indicate that PT. ABC has implemented several green manufacturing practices; however, there are still areas that need improvement, such as high energy consumption and a high defect rate. This study provides recommendations to enhance green manufacturing performance at PT. ABC, including optimizing energy use, reducing waste, and improving production process efficiency. The results of this study are expected to serve as a reference for PT. ABC in developing strategies and improvement plans to achieve better operational and environmental sustainability.